2015
DOI: 10.1007/s00339-015-9196-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat accumulation in microdrilled glass from ultraviolet laser ablation

Abstract: We present numerical and experimental studies of heat accumulation during high-aspect-ratio ultraviolet laser microdrilling of glass. The dependence on pulse repetition rate of the ablation threshold was studied. The rate determines the amount of heat accumulation and temperature variation across the illuminated area. No change in the glass was observed for pulse energies below 1 lJ at 1 kHz; melting occurred at 0.3 lJ, with ablation at 0.7 lJ at 20 kHz. Also, the hole depth doubled when the pulse repetition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Glass modifications have been reported by different approaches including drilling with a Bessel beam [13] and using a CO 2 laser [14]. Very-high aspect ratio holes can be achieved using UV technologies [15][16][17]. However, a huge potential has been predicted for GHz-burst micromachining in dielectrics in a recent review [18], and very recently, first results have been reported on percussion drilling in dielectrics [19].…”
Section: Introductionmentioning
confidence: 99%
“…Glass modifications have been reported by different approaches including drilling with a Bessel beam [13] and using a CO 2 laser [14]. Very-high aspect ratio holes can be achieved using UV technologies [15][16][17]. However, a huge potential has been predicted for GHz-burst micromachining in dielectrics in a recent review [18], and very recently, first results have been reported on percussion drilling in dielectrics [19].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated deep micro drilling in glass using ultraviolet lasers [16][17][18]. In these experiments, the inner surface reflection of the hole enables deep drilling.…”
Section: Introductionmentioning
confidence: 99%
“…The modification mechanism may be considered as follows. First, the fluence where the emission was observed was 2.9 mJ/cm 2 under the beam focused in the glass at a depth of 1100 μm with an absorption coefficient of 90 cm −1 , spot diameter of 7.3 μm (Hidai, et al, 2015a) (same as the calculated beam spot diameter), and reflection at the glass surface of 3.5%. This value is much smaller than that observed for silica glass ablation (Demos, et.…”
Section: Discussionmentioning
confidence: 91%
“…The experimental apparatus was similar to that described in our previous reports (Hidai, et. al., 2015a, Hidai, et.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation